A study of the ability of bioactive extracts from brewers' spent grain to enhance the antioxidant and immunomodulatory potential of food formulations following in vitro digestion. (March 2015) - McCarthy, Aoife L.; O'Callaghan, Yvonne C.; Connolly, Alan; Piggott, Charles O.; FitzGerald, Richard J.; O'Brien, Nora M.
Abstract Bioactivity of a snack-bar, chocolate-drink and yogurt fortified with brewers' spent grain (BSG) phenolic extracts (P2 or B2) or protein hydrolysates (barley protein hydrolysate (BPH), BPH < 3 kDa, BPH < 5 kDa, BPH > 5 kDa) was measured following gastrointestinal in vitro digestion. Concentrations of 0.5 and 0.1% (v/v) digestates were chosen for addition to Caco-2 and Jurkat T cells, respectively. Yogurt and B2 digestate protected against H2O2-induced DNA damage in Caco-2 cells (p < 0.05), by the comet assay. Snack-bar digestates possessed significant (p < 0.05) immunomodulatory effects, measured by ELISA in concanavalin-A stimulated Jurkat T cells. Addition of BPH enhanced (p < 0.05) the IFN-γ reducing capacity of the snack-bar while addition of BPH < 3 and < 5 kDa reduced IL-2 production to a greater extent than unfortified yogurt (p < 0.05). Selected BSG components can enhance the antioxidant and anti-inflammatory potential of foods.